Reimagining the Holy Land: Jerusalem in the 16th Century Antwerp Painting and Graphics - Kurdjukova, Dar’ja E. (Actual Problems of Theory and History of Art, 2021)
The image of Jerusalem as a principal element of Christian art continued to play a big role in the Dutch painting of the 16th century. Usually Jerusalem was represented with temples of more or less fantastic features. From 1515 to 1535, in Antwerp, one of the richest cities of the time in terms of the development of the art market, we find an architectural type (possibly, an allusion on the Holy Sepulchre) atypical of Dutch art, which became very popular amidst the Antwerp Mannerists and some other artists. This architectural type was probably developed as a result of various influences; so, here it is provisionally named the Antwerp type. It is a construction of hybrid features, with a dome and sometimes with gables. The earliest examples can be found in the works of Joachim Patinir and Quinten Massijs. This architectural type became later widespread largely due to Herri met de Bles and his workshop. But starting the mid-16th century, the interest of the Dutch masters generally shifted towards the image of the Tower of Babel, which absorbed, in their view, the features of the Colosseum, due to numerous voyages to Italy and passion for the aesthetics of ruins, as well as to the historical realities of that time. This case investigates the issue of the convergence of various architectural motifs, the evolution of the very idea of a tiered centric building, when Jerusalem sometimes became Rome, and Rome became Babylon (which was largely facilitated, in particular, by engravings made from the drawings by Maarten van Heemskerck). On the one hand, the passion for architectural fantasies was part of the general European process during the Renaissance; on the other hand, it was a reflection of the spirit of Mannerism and the art style that followed it.
Keywords: image of Jerusalem; tower of Babel; painting; graphic arts; Joachim Patinir; Quinten Massijs; Maarten van Heemskerck; architectural motives; Antwerp; Rome; centric building; Errera album; Antwerp sketchbook